2016
DOI: 10.1074/jbc.m116.743856
|View full text |Cite|
|
Sign up to set email alerts
|

Structures of Exopolysaccharides Involved in Receptor-mediated Perception of Mesorhizobium loti by Lotus japonicus

Abstract: In the symbiosis formed between Mesorhizobium loti strain R7A and Lotus japonicus Gifu, rhizobial exopolysaccharide (EPS) plays an important role in infection thread formation. Mutants of strain R7A affected in early exopolysaccharide biosynthetic steps form nitrogen-fixing nodules on L. japonicus Gifu after a delay, whereas mutants affected in mid or late biosynthetic steps induce uninfected nodule primordia. Recently, it was shown that a plant receptor-like kinase, EPR3, binds low molecular mass exopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 58 publications
0
43
0
Order By: Relevance
“…The perception of Nod-factors by legume receptors (NFR) activates nodule initiation and development (Madsen et al, 2003;Radutoiu et al, 2007;Madsen et al, 2011;Broghammer et al, 2012). In addition to Nod-factors, there are other molecules such as surface polysaccharides and proteins secreted by bacterial secretion systems that also play a very important role in the establishment of an efficient symbiosis with the host plant (Janczarek et al, 2015;Kawaharada et al, 2015Kawaharada et al, , 2017López-Baena et al, 2016;Muszy nski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The perception of Nod-factors by legume receptors (NFR) activates nodule initiation and development (Madsen et al, 2003;Radutoiu et al, 2007;Madsen et al, 2011;Broghammer et al, 2012). In addition to Nod-factors, there are other molecules such as surface polysaccharides and proteins secreted by bacterial secretion systems that also play a very important role in the establishment of an efficient symbiosis with the host plant (Janczarek et al, 2015;Kawaharada et al, 2015Kawaharada et al, , 2017López-Baena et al, 2016;Muszy nski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(Ghosh and Maiti ). Two major symbiotically active types of EPS, succinoglycan and galactoglucan, are primarily derived from Sinorhizobium meliloti but have also been isolated from many other rhizobial bacteria (O'Neill et al ; Muszyński et al ). Succinoglycans are a class of acidic polymers composed of eight repeating sugar units containing galactose and glucose residues in a molar ratio of 1 : 7 that are linked by β‐1,3, β‐1,4 and β‐1,6 glycosidic bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to produce extracellular polysaccharide is widespread among rhizobial strains. A number of reports have revealed that rhizobial exopolysaccharide (EPS) plays an important role in symbiosis, including promoting their derived from Sinorhizobium meliloti but have also been isolated from many other rhizobial bacteria (O'Neill et al 1991;Muszy nski et al 2016). Succinoglycans are a class of acidic polymers composed of eight repeating sugar units containing galactose and glucose residues in a molar ratio of 1 : 7 that are linked by b-1,3, b-1,4 and b-1,6 glycosidic bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The symbiosis is a complex process involving an exchange of many signals; among these, legume flavonoids and rhizobial lipochitooligosaccharides play crucial roles (Downie, 2010;L opez-Baena et al, 2016). Lowmolecular-weight (LMW) fraction of extracellular polysaccharide (EPS) secreted by rhizobia is a signal molecule involved in the early stages of symbiosis (Kelly et al, 2013;Kawaharada et al, 2015;Muszy nski et al, 2016). High-molecular-weight (HMW) EPS, which forms the most external layer surrounding the rhizobial cell, protects the bacteria against desiccation, salinity and other stresses (Broos et al, 2005;Jaszek et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…EPS-deficient rhizobia (e.g., Sinorhizobium meliloti, R. leguminosarum bvs. trifolii and viciae and Mesorhizobium loti) induce empty nodule-like structures on compatible host plants, which are inefficient in nitrogen fixation (Rolfe et al, 1996;Cheng and Walker, 1998;Janczarek and Urbanik-Sypniewska, 2013;Muszy nski et al, 2016). However, the importance of EPS in the legume-rhizobium symbiosis depends on the type of the host plant, as indicated by a recent finding that EPS produced by Sinorhizobium fredii HH103 is not required for nodulation of Glycyrrhiza uralensis (Margaret-Oliver et al, 2012;L opez-Baena et al, 2016).…”
Section: Introductionmentioning
confidence: 99%